1988
DOI: 10.1177/004051758805800809
|View full text |Cite
|
Sign up to set email alerts
|

Tetracarboxylic Acids as Formaldehyde-Free Durable Press Finishing Agents

Abstract: 1,2,3,4-Butanetetracarboxylic acid and all- cis-1,2,3,4-cyclopentanetetracarboxylic acid have been studied as durable press reagents for cotton. They quickly form ester-type crosslinks in the cellulose when applied to fabric by pad-dry-cure techniques. Weak bases have proven to be active catalysts, one of the most effective being mono-sodium phosphate. Durable press smoothness ratings of 3.8–4.4 were imparted by either tetracarboxylic acid. The amount of tetracarboxylic acid required could be decreased by two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
156
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(162 citation statements)
references
References 4 publications
3
156
0
3
Order By: Relevance
“…Citric acid is the most extensively studied polycarboxylic acid having advantage of being inexpensive, wide availability, non-toxic and environmentally acceptable. It shows only moderate effectiveness as durable press finishing agent due to the presence of an α-hydroxyl group in its molecule which hinders its esterification with cellulose (Andrews 1990;Andrews et al 1993;Bhattacharyya et al 1999;Kittinaovarut 2003;Schramm and Rinderer 2000;Welch and Peters 1997;Takahashi 2005, 2006). Yellowing of fabric occurs at high curing temperatures (>175 °C) causing dehydration of the citric acid through formation of unsaturated polycarboxylic acids, such as aconitic acid, citraconic acid and itaconic acid; but exposing in open atmospheric moisture reverses the heat induced yellowing process to original whiteness (Choi 1993;Murray 1995;Schramm and Rinderer 1999;Welch and Peters 1999.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Citric acid is the most extensively studied polycarboxylic acid having advantage of being inexpensive, wide availability, non-toxic and environmentally acceptable. It shows only moderate effectiveness as durable press finishing agent due to the presence of an α-hydroxyl group in its molecule which hinders its esterification with cellulose (Andrews 1990;Andrews et al 1993;Bhattacharyya et al 1999;Kittinaovarut 2003;Schramm and Rinderer 2000;Welch and Peters 1997;Takahashi 2005, 2006). Yellowing of fabric occurs at high curing temperatures (>175 °C) causing dehydration of the citric acid through formation of unsaturated polycarboxylic acids, such as aconitic acid, citraconic acid and itaconic acid; but exposing in open atmospheric moisture reverses the heat induced yellowing process to original whiteness (Choi 1993;Murray 1995;Schramm and Rinderer 1999;Welch and Peters 1999.…”
mentioning
confidence: 99%
“…Yellowing of fabric occurs at high curing temperatures (>175 °C) causing dehydration of the citric acid through formation of unsaturated polycarboxylic acids, such as aconitic acid, citraconic acid and itaconic acid; but exposing in open atmospheric moisture reverses the heat induced yellowing process to original whiteness (Choi 1993;Murray 1995;Schramm and Rinderer 1999;Welch and Peters 1999. During curing in presence of a catalyst, citric acid forms ester linkage (Welch and Peters 1997;Bhattacharyya et al 1999); cross-links between two cellulose chains firstly by formatting a 5-membered cyclic anhydride as reactive intermediate and then the reaction between cellulose and anhydride intermediate, which is pH dependent (Yang et al 2000).…”
mentioning
confidence: 99%
“…Rowland et al (1967) were the first to provide evidence that carboxylic acids could impart crease recovery to cotton coupled with strength retention. In addition, Welch (1988) demonstrated that 1,2,3,4-butanetetracarboxylic acid (BTCA) was the most effective crosslinking agent for cotton cellulose, imparting high crease recovery values and durability to laundering. However, the relatively high cost of BTCA and the high application temperatures it required has prevented its use in the textile industry on a commercial scale.…”
Section: Crease-resistant Finishing Of Soybean With Polycarboxylic Acidsmentioning
confidence: 99%
“…[1][2][3] In 1988, Welch 4 reported that tetracarboxylic acids, with 1,2,3,4-butanetetracarboxylic acid (BTCA) in particular, are able to form effective crosslinkages in cotton fabrics when salts of certain phosphoruscontaining acids were used as catalysts. 5 Polycarboxylic acids have been the most promising formaldehyde-free crosslinking agents for cotton cellulose among the various new reagents investigated.…”
Section: Introductionmentioning
confidence: 99%
“…5 Polycarboxylic acids have been the most promising formaldehyde-free crosslinking agents for cotton cellulose among the various new reagents investigated. [2][3][4][5][6] Polycarboxylic acids were also used as crosslinking agents for wood pulp cellulose to improve wet strength and dimensional stability of paper. [7][8][9] BTCA has been the most effective crosslinking agent for cotton and wood cellulose.…”
Section: Introductionmentioning
confidence: 99%